Er-doped silica-based waveguides prepared by different techniques: RF-sputtering, sol-gel and ion-exchange - Righini, G. C.; Pelli, S.; Ferrari, M.; Armellini, C.; Zampedri, L.; Tosello, C.; Ronchin, S.; Rolli, R.; Moser, E.; Montagna, M.; Chiasera, A.; Ribeiro, SJL (Kluwer Academic Publ, 2002)
Erbium-activated silica-based planar waveguides were prepared by three different technological routes: RF-sputtering, sol-gel and ion exchange. Various parameters of preparation were varied in order to optimize the waveguides for operation in the NIR region. Particular attention was devoted to the minimization of the losses and the increase of the luminescence efficiency of the metastable I-4(13/2) state of the Er3+ ion. Waveguide properties were determined by m-line spectroscopy and loss measurements. Waveguide Raman and luminescence spectroscopy were used to obtain information about the structure of the prepared films and about the dynamical processes related to the luminescence of the Er3+ ions.
Keywords: dip-coating; erbium; ion-exchange; luminescence spectroscopy; optical amplification; optical waveguides; Raman spectroscopy; RF-sputtering; silicate glasses; upconversion